PERBANDINGAN KEBIJAKAN PAJAK PENGHASILAN ATAS UKM DI INDONESIA DENGAN NEGARA-NEGARA ANGGOTA OECD - Elsie S. Kasim; Thesa A. Purwanto (Program Pendidikan Vokasi Universitas Indonesia, 2014)
Government implement Government Regulation Number 46 Year 2013 regarding Income Tax on Income from Business that Have Certain Gross Circulation with the aim to improve tax compliance. For Small and Medium Enterprises, the application of this rule is expected to facilitate taxpayers in tax reporting. This study will analyze the application of 1% final income tax from the turnover of Small and Medium Enterprises policies. What are the underlying considerations to apply special rules for income tax for Small and Medium Enterprises, simplification of rules and procedures adopted and comparison of the various provisions of the few countries that have been surveyed. The discussion will be conducted on the application of tax policy for small and medium enterprises undertaken by the countries of the Organization for Economic Cooperation and Development (OECD) which has been surveyed. Taxation policy on small and medium enterprises that will be compared among others are income tax exemption to companies with a turnover below the threshold of small businesses; reimbursement of tax forms be presumptive tax calculation; use cash basis accounting system and accounting procedures more simplified.Keywords: Income Tax, SME, OECD.